Identification of a plausible serum uric acid cut-off value as prognostic marker of stroke: the Uric Acid Right for Heart Health (URRAH) study - Tikhonoff, Valérie; Casiglia, Edoardo; Spinella, Paolo; Barbagallo, Carlo M.; Bombelli, Michele; Cicero, Arrigo F. G.; Cirillo, Massimo; Cirillo, Pietro; Desideri, Giovambattista; D’elia, Lanfranco; Ferri, Claudio; Galletti, Ferruccio; et al. (Journal of human hypertension, 2022)
The Working Group on Uric Acid and Cardiovascular Risk of the Italian Society of Hypertension conceived and designed an ad hoc study aimed at searching for prognostic cut-off values of serum uric acid (SUA) in predicting combined (fatal and non-fatal) cerebrovascular (CBV) events in the whole database. The URic acid Right for heArt Health study is a nationwide, multicenter, observational cohort study involving data on subjects aged 18–95 years recruited on a regional community basis from all the territory of Italy under the patronage of the Italian Society of Hypertension with a mean follow-up period of 120.7 ± 61.8 months. A total of 14,588 subjects were included in the analysis. A prognostic cut-off value of SUA able to discriminate combined CBV events (>4.79 mg/dL or >284.91 µmol/L) was identified by means of receiver operating characteristic curve in the whole database. Multivariate Cox regression analysis adjusted for confounders (age, sex, arterial hypertension, diabetes, chronic kidney disease, smoking habit, ethanol intake, body mass index, low-density lipoprotein cholesterol, and use of diuretics) identified an independent association between SUA and combined CBV events in the whole database (HR 1.249, 95% confidence interval, 1.041–1.497, p = 0.016). The results of the present study confirm that SUA is an independent risk marker for CBV events after adjusting for potential confounding variables, including arterial hypertension, and demonstrate that >4.79 mg/dL is a valid prognostic cut-off value.